A new species of the genus Leptobrachella (Anura, Megophryidae) from Guangxi Huaping National Nature Reserve, South China - Huang, Zhong; Zeng, Zhao-Chi; Wang, Hao-Tian; Lyu, Zhi-Tong; Huang, Han-Hui; Liu, Hong; Wang, Jian; Mo, Yun-Ming (Zootaxa, 2026)
A new species of the genus Leptobrachella is described from northern Guangxi, China, which emphasizes the significant and ongoing underestimation of amphibian diversity within the genus in the karst regions of southwestern China. The new species is phylogenetically sister to Leptobrachella maoershanensis in the 16S ribosomal RNA mitochondrial gene, and can be distinguished from all known congeners by a combination of morphological characteristics. It inhabits montane streams (1200–1400 m a.s.l.) in Guangxi Huaping National Nature Reserve and is sympatric with L. dong but segregates reproductively (breeding May–July vs. February–April), suggesting phenological separation as a key isolation mechanism for their coexistence. Leptobrachella cathaya sp. nov. faces severe anthropogenic threats, including habitat degradation from tourism and plantations, necessitating immediate conservation actions such as regulated access and enhanced population monitoring.